Potentially Remediable Shortcomings in the Contemporary Drug Treatment of Migraine - Mervyn Eadie (MDPI AG, 2022)
Despite the availability over the past decade of a number of new pharmaceutical agents with different mechanisms of action from those of the drugs used previously, the contemporary drug therapy of migraine attacks falls rather short of what would be desirable, while the pharmacological attempt to prevent further attacks appears to prove unsatisfactory about as often as it is successful. The present paper explores reasons for these shortcomings in both the earlier and the current drug therapy of the disorder. Significant major contributory factors appear to be an incomplete understanding of the underlying pathogenic mechanisms of the various stages of the migraine attack, less than optimal pharmacokinetic characteristics of many of the drugs used, and migraine sufferers failing to employ the available drugs to their best advantage. New drugs developed in the light of a more complete understanding of the molecular basis of migraine pathogenesis, together with awareness of pharmacokinetic desiderata in relation to treating and preventing migraine attacks, may go some way towards remedying the situation, but patient decision making may prove more difficult to modify.